The Role of the Human Development Index and Economic Growth in East Java 2015-2024 - Miranda, Fiktoria Dita; Prakoso, Albrian Fiky; Andriansyah, Eka Hendi; Musfidah, Heny; Saputra, Deni Trio (International Journal of Emerging Research and Review, 2026)
Objective: This study aims to examine the effect of the Human Development Index (HDI) and economic growth on income inequality in East Java Province over the period 2015–2024. Despite sustained regional economic growth, income inequality remains a persistent issue, indicating that economic progress may not be evenly distributed across society. Method: This research employs a quantitative approach using secondary time-series data obtained from the Central Statistics Agency of Indonesia. The data are analyzed using the Ordinary Least Squares (OLS) regression method to identify the partial and simultaneous effects of HDI and economic growth on income inequality, which is measured using the Gini ratio. Classical assumption tests are conducted to ensure the validity of the regression model. Results: The empirical findings indicate that both HDI and economic growth do not have a statistically significant effect on income inequality in East Java during the study period. The F-test shows significance (p = 0.010), but partial t-tests reveal insignificance for both HDI (p = 0.089) and economic growth (p = 0.308). This statistical pattern significant F-test with insignificant t-tests suggests potential model instability due to the limited sample size (N=10) and omitted variable bias, rather than meaningful economic relationships. Conversely, economic growth shows a positive coefficient, indicating a tendency to increase income inequality. These results suggest that economic growth in East Java has not yet been inclusive and that improvements in human development have not been sufficient to substantially mitigate inequality. Moreover, the HDI coefficient (-6.64E-05) is economically negligible: even a hypothetical 100-point increase in HDI would reduce the Gini ratio by only 0.00664, an effect too small to be policy-relevant.  Novelty: This study tests inclusive growth propositions at the provincial level in Indonesia and shows that aggregate time-series models with limited observations are insufficient to capture the complex links between growth, human development, and inequality in East Java. The findings provide a diagnostic contribution by emphasizing the need for spatially disaggregated data and more advanced econometric approaches in future research.